2003
DOI: 10.1046/j.1399-0039.2003.00139.x
|View full text |Cite
|
Sign up to set email alerts
|

HLA class II diversity in seven Amerindian populations. Clues about the origins of the Aché

Abstract: The study of the HLA variability of Native American populations revealed several alleles specific to one or more of the Latin American indigenous populations. The analysis of Amerindian groups distributed all over the continent might inform about the area of origin and the dispersal of these alleles and shed light on the evolution of this remarkable polymorphism. Moreover, HLA alleles and haplotypes are excellent markers to understand the genetic relationships between populations. For these reasons, we charact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
87
2
3

Year Published

2005
2005
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(103 citation statements)
references
References 44 publications
11
87
2
3
Order By: Relevance
“…Alcântara et al (1995) have reported that the Guarani-M'byá sub-group from Rio das Cobras, in the Brazilian state of Paraná, has a CHE2 C5+ frequency of 45.93% ± 3.80% and when this was compared with the present data (14.40% ± 2.22%), a statistically significant difference was found (c 2 = 51.10; p < 0.0001%). The present data on CHE2 C5+ phenotype frequencies are in the same direction as data previously obtained on the basis of HLA-DRB1 allele frequencies which led to estimates of genetic distances between the M'byá and Kaiowá (0.0410), M'byá and Ñandeva (0.0307) and Kaiowá and Ñandeva (0.0165) (Tsuneto et al, 2003;Petzl-Erler, 2005, pers. comm.).…”
Section: Conditions Exon 2 (D70g G390v) Exon 3 Exon 4 (A539t)supporting
confidence: 86%
See 2 more Smart Citations
“…Alcântara et al (1995) have reported that the Guarani-M'byá sub-group from Rio das Cobras, in the Brazilian state of Paraná, has a CHE2 C5+ frequency of 45.93% ± 3.80% and when this was compared with the present data (14.40% ± 2.22%), a statistically significant difference was found (c 2 = 51.10; p < 0.0001%). The present data on CHE2 C5+ phenotype frequencies are in the same direction as data previously obtained on the basis of HLA-DRB1 allele frequencies which led to estimates of genetic distances between the M'byá and Kaiowá (0.0410), M'byá and Ñandeva (0.0307) and Kaiowá and Ñandeva (0.0165) (Tsuneto et al, 2003;Petzl-Erler, 2005, pers. comm.).…”
Section: Conditions Exon 2 (D70g G390v) Exon 3 Exon 4 (A539t)supporting
confidence: 86%
“…The degree of non-Amerindian admixture was estimated as 17% in the Guarani-Ñandeva and 3% in the Guarani-Kaiowá sub-groups (Tsuneto, 2003) on the basis of the frequency of HLA haplotypes present in Europeans and Africans and only found in Amerindians as due to admixture. Considering the ethnic composition of the 250 Amerindians examined for the D70G variant (64% GuaraniKaiowá and 36% Guarani-Ñandeva), the respective degrees of admixture of these sub-groups and the frequency of 1.5% of this variant in Euro-Brazilians (Chautard-Freire- Maia et al, 1984), the expected frequency for the D70G variant in this Guarani sample (0.12%) due only to European admixture is statistically lower than the one found (c 2 = 9.61; p < 0.01).…”
Section: Conditions Exon 2 (D70g G390v) Exon 3 Exon 4 (A539t)mentioning
confidence: 99%
See 1 more Smart Citation
“…The distinctiveness of the Guarani and Kaingang populations is in line with the results of earlier studies. 25,26 Among the Amerindians, Guarani Ñ andeva had the highest genetic diversity, which agrees with the relatively high amount of gene flow (14%) from nonAmerindians into this population. 25 On the other hand, Guarani M'byá had a lower diversity and the highest levels of LD, possibly reflecting their genetic isolation and the effect of random genetic drift.…”
Section: Discussionsupporting
confidence: 57%
“…Guarani and Kaingang live close to each other but have remarkable genetic and cultural differences. 24,25 Another important feature of these populations is that gene flow from non-Amerindian and other Amerindian populations is low, with the exception of Guarani Ñ andeva, whose admixture was estimated as 14%. 25,26 The aim of this study was to describe STR_MICA and MICA allelic frequencies and MICA-HLA-B-HLA-C associations in the Guarani and Kaingang populations from Brazil, to compare the diversity found with that of other populations and to extract information about the evolution of MICA polymorphism.…”
Section: Introductionmentioning
confidence: 99%